Fractional order sliding mode controller based on supervised machine learning techniques for speed control of PMSM - Fardila Mohd Zaihidee (Tanjung Malim, 2023)
Fractional order sliding mode controller based on supervised machine learning techniques for speed control of PMSM by Fardila Mohd Zaihidee